A Successful Management of 29 year old Female with Left Central Retinal Artery Occlusion due to Manifestation of Primary Antiphospholipid Syndrome - Herman Bagus Trianto; Cesarius Singgih Wahono; Nadia Artha Dewi (Indonesian Rheumatology Association, 2016)
Ocular involvement in Anti Phospolipid Syndrome (APS) includes a broad spectrum of manifestations from the anterior and posterior segment or the presence of neuro-ophthalmologic features. A female, 29 years old, came to ER handled by ophthalmology department, with chief complaint left visual loss suddenly since 4 hours before admission. Investigations revealed stable vital signs, VOD 20/20, VOS 1/300, funduscopy showedpale and cherry red spot on left retina, OCT revealed hyperreflective of left inner retinal layer, IgG aCL 51.7 U/mL (50.8 U/mL in OPD 3 months later), and the other examinations were within normal limit. Patient was diagnosed with Central Retinal Artery Occlusion due toPrimary Antiphospolipid syndrome. She was performed occular massage and anterior chamber paracintesis procedure, and given O2 6-8 lpm NRBM, Timolol 0.5% eye drop left eye bid, acetazolamide 250 mg bid, Kalium Slow Release 1 tab qd, Levofloxacine eye drop 1 drop/hour post surgery. After the result of IgM aCL available, we added warfarin 2 mg qd and aspirin 320 mg qd. Patient was discharged 2 days later as visual acuity improved with VOD 20/20 and VOS 0.5/60. Key words: Central retina artery occlusion, primary anti phospolipid syndrome, anti cardiolipin antibody